SOSIALISASI PENDIDIKAN DEMOKRASI DAN POLITIK BAGI CALON PEMILIH PEMULA DI KABUPATEN SINJAI - Suhardiman Syamsu; Andi Lukman Irwan; A.M. Rusli; Ashar Prawitno (KRITIS : Jurnal Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2022)
Elections are also the will of the people or the desire of the people so that there is a change in the process of selecting leaders through elections with a better and open system both in the presidential and regional head elections. In every election, there will be novice voters who are taking part in the election for the first time or have their right to vote to participate in the implementation of elections, be it presidential elections or regional head elections. The target for this long-term service is the realization of democratic and political education so that political awareness is awakened and they have adequate knowledge so that they can think rationally in making decisions and using political rights consciously and rationally. This Service Program will have been carried out on October 1, 2021 in the form of indoor activities with the Socialization method. the socialization method provided is using a system of lecture methods, simulations, case studies, brainstorming, games, discussions and watching short films. The materials provided are as follows: (a) Democracy and challenges in the Millennial Era, (b) Development of Government Politics in Indonesia, (c) Elections, (d) Politics as a form of love for the homeland and (e) Follow-up plans.